A retrospective study of neonatal mortality in farmed elk. - Pople, N C (2001)
Despite the increasing importance of the Canadian elk industry, the veterinary literature concerning diseases of elk is sparse, in particular for the neonatal period. This study summarizes necropsy findings in 111 farmed elk calves, up to 30 days of age, submitted to the diagnostic laboratory of the Western College of Veterinary Medicine over a 9-year period (990 to 1998). Causes of mortality fit into 3 categories: infectious disease, noninfectious disease, and undetermined. Organisms causing disease included Escherichia coli, Listeria monocytogenes, and Cryptosporidium sp. Starvation, including dehydration, was also a significant cause of mortality. Necropsy records are a useful source of information, but their scope is limited. There is a need for research that determines the prevalence of neonatal elk diseases and identifies risk factors for morbidity and mortality.